Trzy refleksje o dwujęzyczności - Walczak, Bogdan (Poznańskie Spotkania Językoznawcze, 2014)
Following a brief discussion on the understanding of the concept of bilingualism (and diglossia) the author shares with his audience the reflections on the role and significance of bi- and multilingualism in three areas: practical linguistic communication on the global scale, language education and linguistics (theoretical, comparative and descriptive, at the synchronic and diachronic level).